Terrestrial laser scanning improves digital elevation models and topsoil pH modelling in regions with complex topography and dense vegetation. (September 2017) - Baltensweiler, Andri; Walthert, Lorenz; Ginzler, Christian; Sutter, Flurin; Purves, Ross S.; Hanewinkel, Marc
Abstract: Terrestrial Laser Scanning (TLS) has great potential in creating high resolution digital elevation models (DEMs). However, little is known about the properties of TLS derived DEMs covering several hectares in heterogeneous environments compared to conventional airborne laser scanning (ALS) based models and their influence on derived products. We investigated the accuracy of DEMs with different resolutions derived from TLS and high quality ALS on a study site with complex micro-topography covered by dense forest and ground vegetation. We further examined the effect of these DEMs on predicted topsoil pH using linear regression models built on terrain attributes. We show that at high resolutions (∼1 m), TLS based DEMs performed better than ALS DEMs, which directly translated into significantly better pH models, the best of which showing an R 2 of 0.62. The use of TLS therefore improves the quality of terrain attributes, which are the foundation for many ecological and hydrological applications. Highlights: Accuracy assessment of DEMs derived from terrestrial and airborne LiDAR. Effect of DEMs accuracies and resolutions on soil pH prediction models. Very high resolution DEMs derived from TLS were more accurate than ALS based DEMs. Most accurate topsoil pH models were derived from TLS data. TLS is the favorable option to derive DEMs for complex areas of a few hectares.